Moderating Effect of Perceived Behavioural Control on Tourists’ Revisit Intention in Island Tourism Industry: A Conceptual Model - ROSLI, Nur Akmal; ZAINUDDIN, Zaliha; YUSLIZA, Mohd Yusoff; MUHAMMAD, Zikri; SAPUTRA, Jumadil; NORDIN, Aleff Omar Shah; HAMID, Shahriman Abdul (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.13.8(64).15, 2022)
Seeking enjoyment or pleasure through travelling has been known to reduce stress and improve emotional well-being. However, the prolonged global pandemic and its negative affect have impacted tourists’ travel behaviour and intention. Hence, it is necessary to investigate how and to what extent emotional well-being influences revisit intention. Since studies regarding this topic in the context of island tourism are scarce, the current study extended the TPB model by proposing the influence of positive affect on tourists’ revisit intention to coastal tourism destinations. Moreover, this work explored the moderating role of perceived behavioural control (PBC) on attitude, subjective norms, and behavioural intention. This study enriches the tourism literature related to coastal tourism and tourists’ decision making process. The findings provide useful insights for policy makers and practitioners in the field of the tourism industry and human behaviour.